2016
DOI: 10.1371/journal.pone.0146349
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Methanol, Ethanol and Supercritical CO2 Extracts of Philippine Piper betle L. on Clinical Isolates of Gram Positive and Gram Negative Bacteria with Transferable Multiple Drug Resistance

Abstract: Piper betle L. has traditionally been used in alternative medicine in different countries for various therapeutic purposes, including as an anti-infective agent. However, studies reported in the literature are mainly on its activities on drug susceptible bacterial strains. This study determined the antimicrobial activities of its ethanol, methanol, and supercritical CO2 extracts on clinical isolates of multiple drug resistant bacteria which have been identified by the Infectious Disease Society of America as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 26 publications
6
31
3
6
Order By: Relevance
“…We observed that four of five examined plants, including P. guajava, P. amanus, P. betel, and R. tomentosa, showed antibacterial activities at different levels. These results were similar to previous studies that reported these plants' effects on bacteria [31][32][33][34][35][36][37] and further give evidence to explain their Vietnamese ethnic applications in bacterial diseases [12,13]. In addition, our results demonstrated that among all tested plants, P. amanus and R. tomentosa had outstanding effects on AHPND-caused bacteria, as they always represented the strongest activities, regardless of applied investigation methods (agar disc diffusion or broth dilution) and also regardless of tested strains (V. parahaemolyticus …”
Section: Discussionsupporting
confidence: 92%
“…We observed that four of five examined plants, including P. guajava, P. amanus, P. betel, and R. tomentosa, showed antibacterial activities at different levels. These results were similar to previous studies that reported these plants' effects on bacteria [31][32][33][34][35][36][37] and further give evidence to explain their Vietnamese ethnic applications in bacterial diseases [12,13]. In addition, our results demonstrated that among all tested plants, P. amanus and R. tomentosa had outstanding effects on AHPND-caused bacteria, as they always represented the strongest activities, regardless of applied investigation methods (agar disc diffusion or broth dilution) and also regardless of tested strains (V. parahaemolyticus …”
Section: Discussionsupporting
confidence: 92%
“…1 filter paper) and the methods used were based on methods adopted by Adekunle and Ikumapayi (2006) and Valle et al (2016).…”
Section: The Antifungal Assaymentioning
confidence: 99%
“…One of the promising ways to reduce health hazards and economic losses due to the food-borne microorganisms is the use of natural and organic antimicrobials, such as natural plant compounds (Sirsat et al, 2009). In particular, ethanol solution extracts of different plants have been proposed to control food pathogens (Serio et al, 2014) and multidrug resistant bacteria (Valle et al, 2016). Euodia ruticarpa (A.…”
Section: Introductionmentioning
confidence: 99%